ANALISIS DATA GAYA BERAT DI DAERAH BENDAN DUWUR SEMARANG - Sugita, M. Iqbal; Janah, Anisa Furtakhul; Rahmawati, Dewi; Supriyadi; Khumaedi (Journal of Research and Technology, 2020)
This study was about the gravity in the area of ​​Bendan Duwur, Gajah Mungkur, Semarang. The method used in this research was gravity. The following steps in this activity were: calculating the value of Reader Gravity (gobs), Free Air Correction (FAC), Free Air Anomaly (FAA), Bouguer Correction (BC), Simple Bouguer Anomaly (SBA), Terrain Correction (TC), and Complete Bouguer Anomaly (CBA). The results of this research were listed as the Duwur bendan area, which can be seen from the shape of the points contained in the CBA, which is the smallest mGal value, 2.78 and the largest was 14.14. This can be assessed as an anomaly value, blue was the lowest value while pink the highest value, and yellow was the medium category. Based on the results of gravity measurements in the Bendan Duwur area, Semarang, the smallest mGal value was recognized by the TC compared to the gobs, FAC, FAA, and BC values. TC was producing 0.24 and the highest value was 1.13. The largest correction value was the FAC, the lowest value of mGal was 16.14, while the highest value of mGal was 26.33. Adapters for the Bendan Duwur soil structure based on CBA including the underground category generated were directly related to tectonic activity, but were more related to geology that requires special sedimentation and anthropogenic activities such as water needed.